FRI0115 Ever-smoking is associated with disease severity and opioid use in rheumatoid arthritis. (15th June 2017) - Karellis, A; Rampakakis, E; Sampalis, JS; Cohen, M; Starr, M; Ste-Marie, P; Shir, Y; Ware, M; Fitzcharles, M-A
Abstract : Background: Cigarette smoking, both current and past, is a risk for incident rheumatoid arthritis (RA), even for those with low exposure rates of 1–10 pack years. Current smoking is also associated with severity of disease and poorer response to treatments. It is however not known whether any exposure to cigarettes impacts disease expression, especially for those who have discontinued smoking. Objectives: To assess the disease severity in RA according to smoking status (ever-, past-, current-, non-smoker). Methods: As part of a study to examine cigarette and marijuana smoking in rheumatic disease patients, consecutively attending rheumatology patients completed an anonymous self-administered questionnaire including: pain severity on visual analog scale (VAS), patient global assessment (PtGA) and cigarette or marijuana smoking status. Concomitant physician recorded information included: sociodemographics, co-morbidities, treatments for RA, physician global assessment (PGA). Patients were categorized according to smoking status. Categorical variables were compared between groups with the Chi-Square test and continuous variables with the Student's t-test. Variables showing a statistical trend (p<0.15) in univariate analysis were considered in multivariate logistic regression. Results: Over a 2-month period (April-May 2014), there were 248 (25%) RA attendees of 1000 participants. Significant differences were observed between current, past and non-smokers in regard to age [mean (SD): 59.5 (10.0) vs. 65.2 (10.6) vs. 61.0 (18.2) years; p=0.034], gender (male: 23.9% vs. 30.3% vs. 14.6%; p=0.027), unemployment due to disability (13.3% vs. 3.1% vs. 4.9%; p=0.044), number of RA medications [mean (SD): 2.3 (1.1) vs. 2.1 (1.1) vs. 1.8 (1.1); p=0.019], DMARD use (78.3% vs. 82.8% vs. 64.1%; p=0.008), opioid use (19.6% vs. 10.1% vs. 3.9%; p=0.009), pain [mean (SD): 5.0 (3.3) vs. 4.0 (2.9) vs. 3.7 (2.6) cm; p=0.040] and PGA [mean (SD): 3.8 (2.8) vs. 3.1 (2.8) vs. 3.0 (2.4); p=0.039]. Recreational marijuana was used by 3 non cigarette smokers only, with 1 also reporting medicinal marijuana use. Ever smokers vs. non-smokers used a greater number of RA medications [mean (SD): 4.3 (3.0) vs. 3.7 (2.6); p=0.081], were more likely to use DMARDs (81.4% vs. 64.1%; p=0.003) and opioids (13.1% vs. 3.9%; p=0.014), and showed a trend towards more pain [mean (SD): 4.3 (3.0) vs. 3.7 (2.6); p=0.081]. In multivariate analysis, male gender (OR=2.193; p=0.025) and DMARD use (OR=2.376; p=0.010) were significantly associated with ever smoking while opioid use (OR=2.784, p=0.103 for ever smoking; OR=3.561, p=0.074 for current smoking) showed a statistical trend. Conclusions: Current, but also ever cigarette use, was associated with worse RA disease as indicated by the use of more drug categories, and more likely use of DMARDs to treat RA, and a trend to more pain and opioids. The combination of opioids and cigarettes may be a manifestation of a patient "chemical coping" strategy in RA patients. Disclosure of Interest: None declared